A checklist of the cicadas (Hemiptera: Cicadidae) of Hainan Island, China, with description of a new species - Yang, Mingsheng; Wei, Cong (Zootaxa, 2013)
A total of 54 cacada species, belonging to 28 genera, nine tribes and three subfamilies of the family Cicadidae, are identified to comprise the cicada fauna of Hainan Island, based on the examination of material collected between 2007 and 2011. One species, Semia hainanensis sp. n., is described as new to science. Nine species are recorded as new to Hainan Island, of which two species, Pomponia subtilita Lee, 2009 and Becquartina bleuzeni Boulard, 2005, are reported for the first time from China. In addition, six species formerly recorded from Hainan are removed from the list of Hainan cicadas. Taxonomic remarks and information on geographic distributions are also provided.